Sobre θεών χείρης: Significado y contexto - Rodríguez Alfageme, Ignacio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2005)
The expression θεών χείρας in Quaestiones convivales 663 b poses several questions for accepting the text as transmitted. It shows a relationship with popular medicine and a poetic colour that are determinative in order to understand its meaning. And also its study allows a new correction for thisPlutarchus’ passage.
Keywords: Plutarchus; popular medecine